CONSTITUTIONAL REGULATION OF FUNDAMENTAL RIGHTS IN THE FEDERAL REPUBLIC OF GERMANY - Yu. I. Leibo (Московский журнал международного права, 2019)
Introduction. The article is devoted the constitutional foundations of the legal status of the individual in the Federal Republic of Germany, some fundamental rights, their content and protection. Particular attention is paid to the institute of restrictions of fundamental rights and freedoms in Germany. Fundamental rights are considered in the interpretation of the Federal Constitutional Court of Germany, the legal doctrine that describes fundamental rights and freedoms. The works of the leading German constitutionalists, as well as the works of domestic researchers are used. The author emphasizes the importance of fundamental rights in the formation and evolution of the democratic constitutional order in Germany. The modern tendencies of development of the institution of rights and freedoms in Germany are analyzed.Materials and methods. The material sources of the study were the provisions of the Basic Law of the Federal Republic of Germany of 1949, the current German legislation, the decisions of the Federal Constitutional Court (Bundesverfassungsgericht) of Germany, international human rights documents ratified by Germany. The works of German and Russian constitutionalists were also used during the research. The methodological basis of the article consists of general and special methods of legal research.Research results. The article analyzes in a detailed form the specifics of the constitutional regulation of fundamental human and civil rights and freedoms in Germany, their current state and prospects for further evolution. Problems related to the protection of rights and freedoms and mechanisms of their guarantees are thoroughly considered. Special attention is paid to the analysis of the resonant decisions of the supreme judicial body of the constitutional control of Germany on the legal status of the individuals in this country.Discussion and conclusions. The author comes to the conclusion that the Basic Law of the Federal Republic of Germany contains a fairly complete catalog of fundamental rights and freedoms, which are an integral part of the democratic constitutional order of Germany. The constitutional legislator provides for the possibility of restricting fundamental rights and freedoms only by law and on the basis of the law. The practice of the Federal Constitutional Court plays a special role in the interpretation of these restrictions. The protection of rights and freedoms is considered by the German constitutional legislator as the most important task of all constitutional bodies of the country. The country’s extensive system of guarantees of fundamental rights makes them very effective and efficient instruments.